2021
DOI: 10.3390/antiox10030465
|View full text |Cite
|
Sign up to set email alerts
|

Old Plant, New Possibilities: Wild Bilberry (Vaccinium myrtillus L., Ericaceae) in Topical Skin Preparation

Abstract: Bilberry represents a valuable source of antioxidant substances responsible for its application for the treatment of different conditions (such as inflammation, cardiovascular disease, cancer, diabetes, and different age-related diseases) associated with increased oxidative stress. As oxidative stress might cause skin impairments, we aim to evaluate a topical preparation containing bilberry leaves extract and bilberry seeds oil, obtained as a byproduct of the food industry. To obtain the extracts, the conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…The ability to reduce ferric ions was measured based on previous articles (Krivokapic et al., 2021 ; Tadic et al., 2021 ) with minor revisions. The stock solutions included 300 mM acetate buffer, pH 3.6, 10 mM 2,4,6‐Tris(2‐pyridyl)‐s‐triazine (TPTZ) solution in 40 mM HCl and 20 mM FeCl 3 .6H 2 O solution.…”
Section: Methodsmentioning
confidence: 99%
“…The ability to reduce ferric ions was measured based on previous articles (Krivokapic et al., 2021 ; Tadic et al., 2021 ) with minor revisions. The stock solutions included 300 mM acetate buffer, pH 3.6, 10 mM 2,4,6‐Tris(2‐pyridyl)‐s‐triazine (TPTZ) solution in 40 mM HCl and 20 mM FeCl 3 .6H 2 O solution.…”
Section: Methodsmentioning
confidence: 99%
“…Resveratrol ( Figure 2 ) was found in the bilberry fruits by two different research groups ( Rimando et al, 2004 ; Može et al, 2011 ) and in the leaves ( Tadić et al, 2021 ). It is worth noting that while cultivated blueberries contain both resveratrol and piceatannol, the latter is missing in bilberries completely ( Rimando et al, 2004 ).…”
Section: Bioactive Constituents Of Vaccinium Myrtillus ...mentioning
confidence: 98%
“…Moreover, the extract reduced the UVA-induced apoptosis, but had no effect against the UVB one ( Calò and Marabini 2014 ). A cream which incorporated both the oil from bilberry seeds and the extract from bilberry leaves improved skin hydration parameter slightly more than placebo cream in a month-long clinical trial on 25 volunteers ( Tadić et al, 2021 ). However, in another very recent study, the bilberry fruit extract was found to reduce the sun protection factor upon incorporation into the tested sunscreens.…”
Section: Uses Of Vaccinium Myrtillus Lmentioning
confidence: 99%
“…For this study, the following herbal drugs were chosen: bilberry fruits and leaves ( Myrtilli fructus , Myrtilli folium , Vaccinium myrtillus L., Ericaceae) and green tea leaves ( Camelliae sinensis non fermentatum folium , Camellia sinensis (L.) Kuntze, Theaceae). Selected plant materials are known for their high PCs content and good antioxidant activity [ 26 , 27 , 28 ]. While green tea leaves and bilberry fruits represent widely commercially used herbal drugs, bilberry leaves are mostly considered as waste products from mechanical harvesting of wild berries [ 29 ].…”
Section: Introductionmentioning
confidence: 99%